Regulation of type 2 immunity by basophils - Voehringer, David (Henry Stewart Talks, 2012)
Relationship of basophils to mast cells and eosinophils, Development and activation of basophils, Basophil-deficient mice, Role of basophils and dendritic cells in Th2 polarization, Anaphylaxis and allergic skin inflammation, Basophil response to helminths and ticks